Investigating the effect of workplace noise exposure on cardiovascular disease risk factors in a power plant industry: A case-control study. - Mohammad-Ghasemi, Mostafa; Dehghani-Bidgoli, Sedighe; Ahmadi, Thelma; Nikbakht, Neda; Heidarifar, Shima; Sadeghi-Yarandi, Mohsen (Work, 2023)
BACKGROUND: Occupational noise exposure is a significant health problem. In addition to hearing impairments, noise as a stressor may cause cardiovascular problems. OBJECTIVE: This study aimed to investigate the effect of exposure to workplace noise on cardiovascular disease risk factors. METHODS: This case-control study was conducted in 2021 in a power plant in Iran. In this study, the health status of 406 employees in both exposed (n = 203) and non-exposed (n = 203) to noise groups was examined for cardiovascular disease risk factors. Also, the trend of changes in the studied variables from 2012 to 2020 in exposed employees was examined. Data were collected from participants' annual physical examinations and occupational noise exposure measurements. To measure the noise in the present study, the KIMO-DB300 noise level meter was used. Data were analyzed in SPSS-26 software. RESULTS: The results revealed that mean fasting blood sugar (FBS), triglyceride, liver enzyme (SGOT), blood pressure, and body mass index were significantly different in the two groups (p-value<0.05). There was no significant difference in the mean of creatinine, cholesterol, and liver enzyme (SGPT) between the two groups (p-value>0.05). In the exposed group, the mean of all studied variables except diastolic blood pressure was statistically different during the study years (p-value<0.05). CONCLUSION: This study demonstrates that exposure to noise above the permissible level can affect the cardiovascular disease risk factors, so it is recommended to apply engineering and management measures like using Hearing Conservation Programme (HCP) to reduce the risk of these diseases with periodically assessing the health status of employees and timely diagnosis.